“Mrs. Chatelaine” vs. “Mrs. Slob”: Contestants, Correspondents and the Chatelaine Community in Action, 1961-1969 - Korinek, Valerie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1996)
AbstractScholars and critics alike have presumed that readers of popular women's magazines were merely passive consumers. That was not the case with Chatelaine magazine. Reader commentary was regularly featured in the magazine and often influenced editorial decisions. This analysis of the Mrs. Chatelaine contest provides a demographic profile of the reading community, an overview of the text and the producers, an examination of the national community of readers created at Chatelaine, it also explores the reaction of “average readers” to products of popular culture. In summary, readers' responded in a host of ways to the periodical. Some enjoyed the preferred meanings offered by the magazine, particularly of traditional fare (like the contest) which celebrated paragons of feminine virtue. Other readers were resistant to this material - they criticised, challenged, or parodied the contest - clearly demonstrating that “average” readers did not passively accept material which was at odds with their lives.